People Are Slow to Adapt to the Warm Glow of Giving. (February 2019) - O'Brien, Ed; Kassirer, Samantha
People adapt to repeated getting. The happiness we feel from eating the same food, from earning the same income, and from many other experiences quickly decreases as repeated exposure to an identical source of happiness increases. In two preregistered experiments ( N = 615), we examined whether people also adapt to repeated giving—the happiness we feel from helping other people rather than ourselves. In Experiment 1, participants spent a windfall for 5 days ($5.00 per day on the same item) on themselves or another person (the same one each day). In Experiment 2, participants won money in 10 rounds of a game ($0.05 per round) for themselves or a charity of their choice (the same one each round). Although getting elicited standard adaptation (happiness significantly declined), giving did not grow old (happiness did not significantly decline; Experiment 1) and grew old more slowly than equivalent getting (happiness declined at about half the rate; Experiment 2). Past research suggests that people are inevitably quick to adapt in the absence of change. These findings suggest otherwise: The happiness we get from giving appears to sustain itself.